Correlation between Concrete Compressive Strength and Rebound Number of River Bed and Crusher Run Coarse Aggregate in Pokhara Valley - Katuwal, Tek Bahadur (Technical Journal, 2019)
Concrete is principally composed of the mixture of cement, fine and coarse aggregates, and water and widely used for every building structure and other infrastructure. Aggregate has important functions as concrete making materials for the hardness and strength of concrete. The objective of this research was co – relation of compressive strength of concrete with Rebound number of crusher and river bed coarse aggregate in respect to the M20 grade of concrete with nominal mix. For this research, sample were taken from Hemja Crusher (HC), Hemja River Bed (HR), Kotre Crusher (KC), Kotre River Bed (KR) and considering sand from single source and commercially available single brand OPC cement. Fifteen cubes (150 mm × 150 mm×150mm) were cast for each sampled sources and the Compressive strength and Rebound number was determined after 7 days, 14 days and 28 days of curing. In this research, statistical analysis was carried out to determine the best fit curve by using IBM SPSS. Finally the outcomes of this research indicated that the relationship between rebound number and compressive strength curve is liner.